Effects of group size on school structure and behaviour in yellow‐eyed mullet Aldrichetta forsteri. Issue 5 (12th March 2018) - Middlemiss, K. L.; Cook, D. G.; Jerrett, A. R.; Davison, W.
Abstract : Schooling behaviour in yellow‐eyed mullet Aldrichetta forsteri, a common fish species in New Zealand estuarine habitats, was investigated to identify interaction rules associated with group formation. Tank‐based three‐dimensional studies of three group sizes (15, 75 and 150 individuals) were carried out to measure the effects of these different group sizes on school structure during control, predation risk and foraging behavioural states. Increased group size positively correlated with nearest‐neighbour distance in control and foraging states. Swimming speed was the lowest in all three behavioural states in groups of 15 fish compared with 75 or 150. Immediate behavioural response following visual exposure to a simulated avian predator differed between groups resulting in loss of structure in larger groups. School shape was an oblong–oblate spheroid with a length, breadth and height ratio of 5:2:1 and the area of free space surrounding individual fish was spherical in shape with a high degree of spatial isotropy present in all size groups. These findings challenge traditional theories based on either local or global properties as key drivers of group structure. Instead, our results suggest that a more collaborative approach involving both group size and rules pertaining to nearest‐neighbour interactions affects collective behaviours in this species.